A novel study on a centrifugal humidifier for building cooling. Issue 11 (1st December 2022) - Suranjan Salins, Sampath; Kumar, Shiva; Reddy, S.V. Kota; Nair, Prasanth Sreekumaran
ABSTRACT: Current work mainly deals with the design and construction of a centrifugal humidifier where the humidification and cooling are due to the soaking of the packing and the dispersion of the water from packing due to the centrifugal effect. Celdek pad 7090 is used as humidifying media, and water is used as a working substance. Experiments are performed by varying the water flow rate (WFR), air velocity (AV) and rotational packing speed. Performance parameters such as a difference in dry bulb temperature (DBT), difference in relative humidity (RH), saturation efficiency, coefficient of performance (COP) and evaporation rate (ER) are evaluated. Results showed that a water flow rate of 0.6 litres per minute (L/min), rotor speed of 150 rpm and air flow rate of 5 m/s gave the maximum performance. The current unit gave a maximum cooling efficiency, COP and ER equal to 79.23%, 5.24 and 0.90 g/s, respectively. Stationary and dynamic packing conditions are assessed where it is observed that the performance of dynamic packing is higher than that of the static case at all operating ranges. Celdek packing with dynamic conditions can be suitably applied to handle huge cooling loads, which encourages sustainable energy sources and reduces environmental pollution by limiting greenhouse gas emissions.